Položaj ločitvenih upnikov v stečaju - Balažic, Vlado (Podjetje in delo, 2013)
The initiation of bankruptcy proceedings has no influence on the existence of a claim and a right to separate settlement. However, a creditor may enforce his claim against the debtor in bankruptcy even if it is secured with the right to separate settlement only in bankruptcy proceedings and pursuant to the rules of such procedure, unless otherwise provided for by the law in respect of a particular case. As a general rule a creditor has to lodge his right to separate settlement within the same time limit as prescribed for the lodging of a claim, i.e. within three months following the publication of the notice. The method of payment of the secured claim depends on the question if the creditor had lodged his claim and the right to separate settlement within the prescribed time limit and if they were negated.Acquisition of the right to separate settlement can also be a challengeable. A speciality of such action is the fact that the acquisition of the right to separate settlement, occurring through entry in the land register, can be challenged only with a cancellation complaint. However, at the same time it is not necessary to challenge the binding legal transaction, but only the effects of the disposable legal transaction, so that by the cancellation complaint retaliatory claim is enforced.Dissolution of a legal entity due to the termination of the bankruptcy proceedings or cancellation from the court register without liquidation does not result in the termination of its liabilities. Consequently, it also does not result in the termination of the mortgage debtors liabilities.
Keywords: stečaj; stečajni upniki; terjatve; zavarovanje